Induction of Labor Using Castor Oil Cocktail – an Analysis of Real-world Data - Ziegler, Stefanie Mona; Heimann, Yvonne; Schleussner, Ekkehard; Weschenfelder, Friederike; Groten, Tanja (Geburtshilfe und Frauenheilkunde, 2024)
Induction of labor is indicated when benefits of delivery outweigh benefits of prolonged pregnancy, which is not always welcomed by women. Castor oil is accepted as an “old household remedy” for labor induction but is not yet part of the official guidelines. Nevertheless, it is often used, mostly even before the women are admitted to the hospital. Data on its actual benefits and safety are missing. Upon accepting the real-world practice of applying castor oil cocktail for labor induction we added castor oil as one option of labor induction in our clinical routine for multiparous women at term, with a history of at least one vaginal delivery. Here we aimed to generate data on the effectivity and safety of castor oil in labor induction by analyzing the real-world data generated in our cohort.In our retrospective analysis we included data of a cohort of 148 multiparous women induced by castor oil cocktail and of 286 matched controls receiving established methods according to the current guidelines for labor induction. The castor oil cocktail was prepared following a standardized recipe with quality-tested castor oil. Statistical analysis was performed with SPSS 27.0.Perinatal outcome data including the rate of vaginal deliveries did not differ between groups, except significantly more neonates were admitted to the neonatal intensive care unit in the group receiving established methods for induction of labor (p = 0.01). In 39 women (26%), administration of castor oil cocktail alone failed to induce labor. The time from initiation of labor induction until delivery was significantly shorter in the castor oil cocktail group (p = 0.04).Our study demonstrates the safety and effectivity of a castor oil cocktail induction in multiparous women at term in a hospital-based setting using quality-controlled castor oil in a standardized recipe.
Keywords: castor oil; induction of labor; multiparity; postdate pregnancies; inpatients